(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A binary matrix has the Consecutive-Ones Property (C1P) if its columns can be requested so that all 1’s in each row are consecutive. We consider here a variation of the C1P where columns can seem on various occasions in the requesting. Despite the fact that the general issue of choosing the C1P with variety is NP-finished, we present here an instance of enthusiasm for relative genomics that is tractable.